EVALUATION OF READER SERVICES IN THE UNIVERSITY LIBRARIES OF SRI LANKA - PADMASIRI, G.R. (degree of Master of Library Science, 1997)
The study on "Evaluation of Reader Services" in University Libraries is based on existing fifteen University Libraries including the central and faculty libraries of six universities in Sri Lanka. The objectives of the study were to identify and evaluate existing university library services. Questionnaires, Interviews and observation survey methods were employed in the collection of data. University students and academic staff were deemed as the study population. The study revealed that most of the library services should be improved. User education, collection development, reference service, photocopy service, library publications use of new information technology etc., were identified as areas that needed improvement. The study further indicated the improvement of infra-structure facilities such as library buildings, effective communication systems, use of local and international information networks, adequate financial allocations and dedication on the part of the library professional staff are needed to provide improved effective and efficient reader service.